Phthalocyanines as a π–π Adsorption Strategy to Immobilize Catalyst on Carbon for Electrochemical Synthesis - Klunder, Kevin J.; Cass, Ashley C.; Anderson, Scott L.; Minteer, Shelley D. (Synlett, 2019)
In most electrochemical syntheses, reactions are happening at or near the electrode surface. For catalyzed reactions, ideally, the electrode surface would solely contain the catalyst, which then simplifies purification and lowers the amount of catalyst needed. Here, a new strategy involving phthalocyanines (Pc) to immobilize catalysts onto carbon electrode surfaces is presented. The large π structure of the Pc enables adsorption to the sp2-structure of graphitic carbon. TEMPO-modified Pc were chosen as a proof of concept to test the new immobilization strategy. It was found that the TEMPO-Pc derivatives functioned similarly or better than the widely used pyrene adsorption method. Interestingly, the new TEMPO-Pc catalyst appears to facilitate a cascade reaction involving both the anode and the cathode. The first step is the generation of an aryl aldehyde (anode) followed by the reduction of the aryl aldehyde in a pinacol-type coupling reaction at the cathode. The last step is the oxidation of a hydrobenzoin to create benzil. This work demonstrates the unique ability of electrochemistry and bifunctional catalysts to enable multistep chemical transformations, performing both reductive and oxidative transformations in one pot.
Keywords: electrochemistry; phthalocyanines; alcohol oxidation; electrosynthesis; pyrene